2011
DOI: 10.4161/spmg.1.1.13971
|View full text |Cite
|
Sign up to set email alerts
|

Environmental toxicants and male reproductive function

Abstract: environmental toxicants, such as cadmium and bisphenol A (BPA) are endocrine disruptors. in utero, perinatal or neonatal exposure of BPA to rats affect the male reproductive function, such as the blood-testis barrier (BTB) integrity. This effect of BPA on BTB integrity in immature rats is likely mediated via a loss of gap junction function at the BTB, failing to coordinate tight junction and anchoring junction function at the site to maintain the immunological barrier integrity. This in turn activates the extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
104
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 138 publications
(114 citation statements)
references
References 79 publications
(123 reference statements)
6
104
0
4
Order By: Relevance
“…Environmental toxins can impair the viability and function of Sertoli cells, inducing BTB disruption. [109][110][111] Our findings demonstrate that ZO-1 and Cx43 were targeted by AgNPs, as evidenced by the decreased level of their mRNA in TM4 cells exposed to AgNPs, whereas Ocln-11 did not show significant changes ( Figure 10B). Vimentin expression is considered an indicator of the early effects of testicular toxins.…”
mentioning
confidence: 67%
“…Environmental toxins can impair the viability and function of Sertoli cells, inducing BTB disruption. [109][110][111] Our findings demonstrate that ZO-1 and Cx43 were targeted by AgNPs, as evidenced by the decreased level of their mRNA in TM4 cells exposed to AgNPs, whereas Ocln-11 did not show significant changes ( Figure 10B). Vimentin expression is considered an indicator of the early effects of testicular toxins.…”
mentioning
confidence: 67%
“…Essentially, the dynamic nature of spermatogenesis requires AJs to act rapidly to extracellular stimuli in order to permit a timely passage of developing germ cells across the seminiferous epithelium from the basal to the adluminal compartment (Yan et al 2008). Therefore, the half-life of AJs component proteins is usually short and thereby Sertoli germ cell contacts are subject to extensive alteration and remodeling (Cheng et al 2011). In addition, EGF signaling has been identified as one of the earliest signal transduction events occurring near the cell membrane in response to different stress conditions (Cai et al 1998, Zhang & Jope 1999, Murshid et al 2011.…”
Section: Role Of Egf In Testicular Ischemia-reperfusion Injurymentioning
confidence: 99%
“…Most of the samples exhibited an alteration in their testicular structure with an extensive degeneration in the testes, a major reduction in the tubules of the spermatogenic lines, and with a local atrophy of the germinal epithelium, and remains of germinal cells and inflammatory processes inside the tubules (Mandich et al 2007;Al-Sakran et al 2016;Li et al 2016). There are other studies in which it was observed that the alteration in the blood-testis barrier at 200µM perturbed the tight junction of sustentacular cells (Cheng et al 2011). This differs from what was observed in rats after exposure to 20 and 100 mg/kg of BPA, where there were no adverse effects on the testicular morphology compared to the control (Nakamura et al 2010).…”
Section: Discussionmentioning
confidence: 91%